Control of a quasi-static MEMS Mirror for raster scanning projection applications - Riccardo Antonello; Roberto Oboe; Daniele D’Elia; Luca Molinari (International Journal of Optomechatronics)
The angular motion of quasi-static micromirrors used for raster scanning projection applications is typically affected by undesired oscillations related to high-frequency resonant modes triggered by the sawtooth-like driving signal. This paper proposes a novel closed-loop tracking controller for improving the linearity of the trace motion, and hence the image brightness. It includes a feedforward action to achieve the required tracking performance under nominal conditions, and a feedback control for robustness against disturbances and other nonidealities. Notch filtering prevents resonance-induced ringing. The simplicity of the architecture enables an easy implementation on FPGA or ASIC. Experimental tests carried out on two different micromirrors with Lead-Zirconate-Titanate (PZT) piezoelectric actuation and piezoresistive sensing demonstrate an average linearity of [Formula: see text] and reproducibility of [Formula: see text] for sawtooth reference trajectories with up to [Formula: see text] amplitude and 120 Hz frequency, thus meeting the performance requirements mandated by the standards for high-resolutions projection applications.